The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1021/i100012a009
|View full text |Cite
|
Sign up to set email alerts
|

Laminar film flow over a sphere

Abstract: Ind. Eng. Chem. Fundam. 1983, 22, 405-410 405 H = height of liquid head in the vessel kmd = micromixing parameter k , = characteristic wave number for large-scale eddies L = turbine diameter N = imperller rotational speed N, = quantity of acid segregated N , = quantity of acid completely segregated Nd = quantity of acid segregated in the molecular mixing zone q = volumetric feed rate Re = NL2/u = Reynolds number for mechanically stirred ReA = u[Ag/u = Reynolds number of turbulence Ri = reaction rate Sc = Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…First of all, inertial effects have been neglected in the solution of the momentum equations. In a recent work, Gyure and Krantz (1983) showed that inertial effects were of extreme importance in the problem of free sur-face flow over a sphere. They point out that inertia results in a significant thinning of the liquid film thickness.…”
Section: Aiche Journalmentioning
confidence: 99%
“…First of all, inertial effects have been neglected in the solution of the momentum equations. In a recent work, Gyure and Krantz (1983) showed that inertial effects were of extreme importance in the problem of free sur-face flow over a sphere. They point out that inertia results in a significant thinning of the liquid film thickness.…”
Section: Aiche Journalmentioning
confidence: 99%
“…However previous studies of thin film flow over a sphere were confined purely to the hydrodynamic problem. Gyure & Krantz [14] used a perturbation analysis for low Reynolds numbers. Gribben [15] obtained an approximation by using the Pohlhausen integral momentum technique [16], which assumed an approximate velocity profile across the thickness of the film.…”
Section: Introductionmentioning
confidence: 99%
“…However previous studies of thin film flow over a sphere were confined purely to the hydrodynamic problem. Gyure & Krantz [1] used a perturbation analysis for low Reynolds numbers. Gribben [2] obtained an approximation using the Pohlhausen integral momentum technique, which assumed an approximate velocity profile across the thickness of the film; Hunt [3] obtained a numerical solution using the modified Keller box method, which accommodated the outer, free boundary.…”
Section: Introductionmentioning
confidence: 99%